Temperament predšolskih otrok v povezavi z njihovim socialnim vedenjem - Rola, Tjaša (Revija za elementarno izobraževanje, 2019)
The aim of this research is to explain the role of a child's temperament in his emotional and social adaptation. The data was obtained with the Social Competence and Behavior Evaluation Scale and the Children's Behavior Questionnaire. The study included 144 children aged between 36 and 79 months. The results show a tendency for surgency to be positively associated with the externalisation of problems, but the relation was not statistically significant. It was established that children who express more negative affectivity are also more anxious; however, it was not possible to confirm the statistical significance of the relation between negative affectivity and aggressiveness. The results also show that shyness is positively associated with the internalisation of problems and effortful control of social competence and cooperation with adults.
Keywords: predšolski otroci; socialno vedenje; temperament